Interactive eduplay in fostering early childhood cognitive development: Insights from a qualitative field study - Winnuly Winnuly; Fifi Khoirul Fitriyah; Nisaul Barokati Selirowangi; Reviana Reviana; Tria Margareta (Journal of Research in Instructional, 2026)
This study aims to analyze the implementation of interactive eduplay as an educational learning medium in supporting early childhood cognitive development at Raudhatul Athfal Muslimat NU Al-Amin Sugio. The research is motivated by the need for innovative learning media that is able to provide optimal stimulation according to the characteristics of early childhood learning in the modern era. This study uses a qualitative approach with subjects of students aged 5–6 years. Data was collected through observation, interviews, and documentation, then analyzed using thematic analysis techniques. The results of the study identified three theme areas including preparation, implementation and evaluation as well as five main themes, namely (1) readiness for the implementation of interactive eduplay, (2) improving children's cognitive abilities, (3) increasing motivation and learning involvement, (4) the role of teachers as learning facilitators, and (5) collaboration between schools and parents in providing stimulation of children's development. The findings show that the use of interactive eduplay not only improves children's ability to recognize letters, numbers, colors, shapes, and logical thinking skills, but also encourages the formation of an active, fun, and child-centered learning experience.